Possible role of calcitonin gene‐related peptide in trigeminal modulation of glomerular microcircuits of the rodent olfactory bulb. (5th January 2017) - Genovese, Federica; Bauersachs, Hanke Gwendolyn; Gräßer, Ines; Kupke, Janina; Magin, Laila; Daiber, Philipp; , Sertel‐Nakajima; Möhrlen, Frank; Messlinger, Karl; Frings, Stephan
Abstract: Chemosensation in the mammalian nose comprises detection of odorants, irritants and pheromones. While the traditional view assigned one distinct sub‐system to each stimulus type, recent research has produced a more complex picture. Odorants are not only detected by olfactory sensory neurons but also by the trigeminal system. Irritants, in turn, may have a distinct odor, and some pheromones are detected by the olfactory epithelium. Moreover, it is well‐established that irritants change odor perception and vice versa . A wealth of psychophysical evidence on olfactory‐trigeminal interactions in humans contrasts with a paucity of structural insight. In particular, it is unclear whether the two systems communicate just by sharing stimuli, or whether neuronal connections mediate cross‐modal signaling. One connection could exist in the olfactory bulb which performs the primary processing of olfactory signals and receives trigeminal innervation. In the present study, neuroanatomical tracing of the mouse ethmoid nerve illustrates how peptidergic fibers enter the glomerular layer of the olfactory bulb, where local microcircuits process and filter the afferent signal. Biochemical assays reveal release of calcitonin gene‐related peptide from olfactory bulb slices and attenuation of cAMP signaling by the neuropeptide. In the non‐stimulated tissue, the neuropeptide specifically inhibited the basal activity of calbindin‐expressing periglomerular interneurons, but did not affect the basal activity of neurons expressing calretinin, parvalbumin, or tyrosine hydroxylase, nor the activity of astrocytes. This study represents a first step toward understanding trigeminal neuromodulation of olfactory‐bulb microcircuits and provides a working hypothesis for trigeminal inhibition of olfactory signal processing. Abstract : Stimulation with irritants impedes the processing of olfactory signals. This paper provides evidence that the olfactory bulb is a site of interaction between the trigeminal and olfactory systems. The ethmoidal branch of the trigeminal system invades the olfactory bulb and innervates 50% of the glomeruli with peptidergic fibers. CGRP released from these fibers inhibits glomerular circuit activity, possibly by targeting pacemaker neurons, the external tufted cells. This neuromodulatory pathway may contribute to chemosensory cross‐talk in rodents.